El deseo individual de (más) hijos y su concordancia en el interior de los núcleos conyugales en México - Regules García, Ricardo; Escoto Castillo, Ana Ruth (El Colegio de México A.C., 2018)
In this paper, we analyze whether the desire to have (more) children of one member of the conjugal nucleus predicts the desire of the other member. We investigate the sociodemographic and contextual variables that interfere with agreement within the conjugal nuclei and we analyze whether the sex of live born children (LBC) is linked to the individual desire to have (more) children, and to the concordance or discrepancy between the wishes of members of the conjugal nucleus. The analysis of the data obtained from the National Survey on Household Living Standards (ENNViH) showed a significant association between the composition by sex of LBC, the desire of the spouses to have more children, and agreement within the couple regarding future reproduction plans.